Action research : teachers as researchers in the classroom - Mertler, Craig A. (SAGE, 2009)
"The Second Edition of Action Research: Teachers as Researchers in the Classroom introduces practicing teachers to the process of conducting classroom-based action research. Written for the practicing educator, the focus is on conducting applied, classroom research. The book s practicality stems from its attention to research methods and procedures that teachers can use with their everyday instructional practices and classroom activities."--BOOK JACKET